NEGARA DAN LEMAHNYA GOVERNABILITY Studi Eksploitasi Pasir Galunggung di Kecamatan Sukaratu Tasikmalaya - Subhan Agung (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Weak government control of sand mining business people showed weak governability Galunggung government. The government should be able memoderatori private competition that harm the public interest. Based on the realities on the ground, people are "fed up" with the exploitation of sand Galunggung who reap the negative effects, even in the long run fear it would remove the potential for community livelihoods.The government should immediately be able to control the business include reclaiming land that was unused. Data collection methods used in this field study using observation and documentation media. Analyses were performed by using descriptive method-interactive between one datum to another datum, and between the data with theory.